PENGARUH KOMITMEN ORGANISASI, BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI KANTOR DINAS KETAHANAN PANGAN PEKANBARU RIAU - Nesa, Nasari; Zulfadill, Zulfadill; Arwinence, Pramadewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2024)
This research aims to determine the influence of organizational commitment,organizational culture and work motivation partially and simultaneously onemployee performance at the Pekanbaru Riau Food Security Service Office. Thepopulation for this study were all employees at the Pekanbaru City Food SecurityService Office with a total of 55 people. The sampling technique uses the censustechnique. The data collection technique uses a questionnaire which is analyzedusing multiple linear regression. The research results show that organizationalcommitment, organizational culture and work motivation partially andsimultaneously influence employee performance at the Pekanbaru Riau FoodSecurity Service Office. Organizational commitment, organizational culture andwork motivation simultaneously have a significant effect on employeeperformance with the percentage influence of the three variables together being58.8% while the remaining 41.2% is explained by other variables not examined inthis research. Keywords: Commitment, Culture and Motivation, Employee Performance